Potential Utilisation of Theobroma cacao Pod Husk Extract: Protective Capability Evaluation Against Pollution Models and Formulation into Niosomes - Erika Chriscensia; Joshua Nathanael; Urip Perwitasari; Agus Budiawan Naro Putra; Shakila Angjaya Adiyanto; Pietradewi Hartrianti (Tropical Life Sciences Research, 2024)
Theobroma cacao L. beans have long been used for food and medicinal purposes. However, up to 52%–76% of Theobroma cacao L. fruit comprises its husk, which are regarded as waste and oftentimes thrown away. In fact, cocoa pod husks actually possess a high antioxidant capacity. Antioxidants can be used to fight free radicals that are produced by environmental pollution. In order to simulate the effects of pollution, H2O2 and cigarette smoke extract models were used respectively. However, the antioxidant properties are limited on the skin due to poor penetration. Hence, in order to increase the topical penetration, cocoa pod husk extract (CPHE) was also formulated into niosomes thereafter. CPHE was characterised using total phenolic content, total flavonoid content and three antioxidant assays. After that, cytotoxicity and cytoprotective assay were conducted on HaCaT cells, which represent the skin epidermis. CPHE was then formulated into niosomes subjected to stability and penetration studies for three months. CPHE was shown to contain 164.26 ± 1.067 mg GAE/g extract in total phenolic content and 10.72 ± 0.32 mg QCE/g extract in total flavonoid content. In addition, our results showed that CPHE possesses similar antioxidant capacity through 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, around eight-fold less through ABTS assay and approximately twelve-fold less through Ferric reducing power (FRAP) assay. The extract also showed comparable cytoprotective properties to that of standard (ascorbic acid). The niosome formulation was also able to increase the penetration compared to unencapsulated extract, as well as possess a good stability profile. This showed that CPHE, in fact, could be repurposed for other uses other than being thrown away as waste.